Accessibility and transcreation in museum translations: a case study of National Gallery Singapore - Ang, Jocelyn Peixun (Nanyang Technological University, 2023)
Translation is an important aspect in the function of cultural institutions such as museums. It allows museums to fulfil their function in archiving historically and culturally significant objects, and allows the public to have relatively equitable access to art, heritage and culture.